2002
DOI: 10.1002/syn.10158
|View full text |Cite
|
Sign up to set email alerts
|

Regional infusions of serotonin into the striatum and memory consolidation

Abstract: Lesions, temporal inactivation, electrical stimulation and administration of drugs that antagonize synaptic activity of the striatum lead to significant deficits of memory. Also, it has been shown that interruption of dopaminergic, GABAergic, or cholinergic activity in discrete areas of this structure is sufficient to disrupt cognitive functions. In spite of the known interactions among dopamine, GABA, acetylcholine, and serotonin, there is a notable scarcity of data germane to the participation of striatal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…5-HT 3 antagonists or 5-HT 4 agonists (systemic or central) improved PA learning and/or prevented scopolamine-or hypoxic-induced amnesia. In addition, 5-HT posttraining injections into the dorsal and ventral striatum selectively produced strong amnesia in PA (Prado-Alcala et al 2003). Izquierdo and colleagues have demonstrated that both cyclic adenosine monophosphate (cAMP) and protein kinase C (PKC) changes are necessary for the initiation and continuity of long-term memory consolidation in the PA task, which is modulated by diverse neurotransmission systems and transduction pathways, including 5-HT 1A synapses in the CA1 hippocampal area, as well as the entorhinal and posterior parietal cortex (see Izquierdo and McGaugh 2000;McGaugh and Izquierdo 2000).…”
Section: Learning and Memory 369mentioning
confidence: 97%
“…5-HT 3 antagonists or 5-HT 4 agonists (systemic or central) improved PA learning and/or prevented scopolamine-or hypoxic-induced amnesia. In addition, 5-HT posttraining injections into the dorsal and ventral striatum selectively produced strong amnesia in PA (Prado-Alcala et al 2003). Izquierdo and colleagues have demonstrated that both cyclic adenosine monophosphate (cAMP) and protein kinase C (PKC) changes are necessary for the initiation and continuity of long-term memory consolidation in the PA task, which is modulated by diverse neurotransmission systems and transduction pathways, including 5-HT 1A synapses in the CA1 hippocampal area, as well as the entorhinal and posterior parietal cortex (see Izquierdo and McGaugh 2000;McGaugh and Izquierdo 2000).…”
Section: Learning and Memory 369mentioning
confidence: 97%
“…Congruent with this expectation, we have recently reported that indeed, intrastriatal administration of PCA produces a marked deficit in retention of inhibitory avoidance (Solana-Figueroa et al, 2002a). Furthermore, activation of intrastriatal 5-HT receptors, induced by infusion of serotonin itself, has the same detrimental effect (Prado-Alcalá et al, 2003). It is not known, however, which of the serotonin receptors within the striatum are involved in memory of aversive events.…”
Section: Introductionmentioning
confidence: 93%
“…Extensive evidence indicates that learning and memory of procedural training depends critically on the dorsal striatum (i.e., caudate nucleus) (Packard and White 1991;Packard et al 1994;Packard and Knowlton 2002;Prado-Alcalá et al 2003;Wachter et al 2009). As we found further that such a striatal administration of corticosterone did not enhance memory of the contextual representations of the apparatus or that of the shock experience per se, such findings suggest the possibility that the corticosterone might have enhanced memory of some procedural or implicit aspects of inhibitory avoidance training.…”
mentioning
confidence: 99%